CYBER SECURITY BEHAVIOR MODEL ON HEALTH INFORMATION SYSTEM USERS DURING COVID-19 PANDEMIC - Penggalih Mahardika Herlambang; Sylvia Anjani; Hendro Wijayanto; Murni Murni (Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
The use of the Health Information System raises the risk of data leakage which is mostly caused by internal health facilities. For this reason, an instrument is needed that can measure the behavior of users who are at risk for the health information system used to minimize the potential for these leaks. Develop and test the validity and reliability of the questionnaire based Human Aspect of Information Security Questionaire (HAIS-Q), Risky Security Behavior Scale (RScB), and the tendency of Internet users in Indonesia. Based on the research 4 aspects that affect the security of Health Information System, namely the use of electronic devices, access to healthinformation systems, internet behavior, and unusual events in health facilities. The questionnaire developed consisted of 27 question items was valid (r count> r table) and reliable (Alfa Chronbach value of 0.777). The developed questionnaire design can be applied to assess the risk of cyber attacks on Health Information Systemsin health facilities. Further research is needed to implement the design of the questionnaire.